PENGEMBANGAN FASILITAS PERTUMBUHAN SPIRITUAL PASIEN DI UNIT HEMODIALISA RUMAH SAKIT SANTA ELISABETH MEDAN - Rusmauli Lumban Gaol (STIKes Santa Elisabeth Medan, 2017)
Standard Operating Procedure (SOP) of Spiritual Growth Facilitation (SGF) is developed to increase patients’ spirituality. The SOP which develops intervention in SGF has to be carried out by nurses, especially in the Hemodialysis Unit of Santa Elizabeth Hospital, Medan. This research used to deployment Standard Operating Procedure (SOP). Nurse intervention that carry patien who is undergoing hemodialys. The research used action research method with with consisted of the stages of reconnaissance, planning, acting, observing,and reflecting. The data were gathered by conducting FGD, distributing quetionnaires, and participant observation. Therewere 10hemodialysis nurse as the participants. The gathered data wereanalyzed qualitatively and quantitatively. The qualitatively data is get from the result of FGD and the result of observation. While the qualitatively data that gatherd from qusetionnaire deployment. This research showed Standard Operating Procedure (SOP) of Spiritual Growth Facilitation that being a model of doing enchancement patient spiritual intervantion who is undergoing hemodialys in hemodialysis unit of Santa Elisabeth Medan. And the possitive impact for knowledge,skills, and act to carry patient who is undrgoing hemodialys. Researcher ask to management of Santa Elizabeth Medan to keep do supervition to elevation contribution SOP in hemodialys Santa Elizabeth Medan.